An Analysis of Livestock Choice : Adapting To Climate Change In Latin American Farms - Seo, Niggol (The World Bank, 2007)
The authors explore how Latin American livestock farmers adapt to climate by switching species. They develop a multinomial choice model of farmer's choice of livestock species. Estimating the models across over 1,200 livestock farmers in seven countries, they find that both temperature and precipitation affect the species Latin American farmers choose. The authors then use this model to predict how future climate scenarios would affect species choice. Global warming will cause farmers to switch to beef cattle at the expense of dairy cattle